Analisis Manfaat Informasi Akuntansi Pada Ukm Di Wilayah Kabupaten Sukoharjo - Jumingan, Jumingan; Rosita, Rosita (Graduasi: Jurnal Bisnis & Ekonomi, 2012)
Lack of ability in using accounting information, is one that causes less useful indicator for SMEs to develop their businesses. The purpose of this study was to determine how useful accounting information for small and medium businesses (SMEs) in Sukoharjo This study is expected to provide empirical evidence about the benefits of accounting information on SMEs in Sukoharjo. The population in this study is the SME Regional Sukoharjo while the sample in this study was 50 respondents are SMEs accounting information systems training. The sampling method study using interviews with responden. data analysis technic by comparing existing theories with interviews, if the results of interviews with a number of theories are not the same then the results of this study means that information is not useful accounting for Sukoharjo SMEs in the region. The results showed that the education / training, accounting information can be useful and can be applied in SMEs Sukoharjo